Artesunate alleviated murine ulcerative colitis by regulating immune response through inhibiting endoplasmic reticulum stress - Yin, Shaojie; Li, Liuhui; Chen, Xiaolan; Wang, Jing; Mao, Yujuan; Wang, Jingxuan; Xie, Xiaoyuting; Li, Jingui; Yang, Haifeng (Frontiers in Immunology, 2025)
Innate and adaptive immunity are intricately linked to the pathogenesis of ulcerative colitis (UC), with dysregulation of the Treg/Th17 balance and M2/M1 macrophage polarization identified as critical factors. Artesunate (ARS) has previously been shown to alleviate UC by inhibiting endoplasmic reticulum stress (ERS). To further investigate the regulatory effects of ARS on immune dysregulation associated with colitis and the role of ERS in this process, an experimental colitis model was established using dextran sulfate sodium (DSS). Flow cytometry was employed to assess changes in the Th17/Treg cell ratio in the spleen and macrophage polarization in the intestine, while RT-qPCR was used to quantify the transcription levels of relevant genes in colonic tissues. ARS treatment significantly mitigated DSS-induced pathological damage, reduced the proportion of CD4+Th17 cells, and downregulated the mRNA expression of IL-17A, IL-17F, and RORγt, while concurrently increasing the proportion of CD4+Treg cells and upregulating TGF-β expression. Additionally, ARS restored the DSS-induced decline in the M2/M1 macrophage ratio and enhanced the transcription of Arg-1 and IL-10, while suppressing the expression of pro-inflammatory markers, including iNOS, IL-1β, IL-6, and TNF-α. Notably, co-treatment with 4-phenylbutyric acid (4-PBA, ERS inhibitor) augmented the immunoregulatory effects of ARS, whereas 2-deoxy-D-glucose (2-DG, ERS agonist) co-treatment counteracted its protective activity against UC. These findings suggest that ERS plays a crucial role in mediating the therapeutic effects of ARS on UC, particularly by modulating Th17/Treg balance and macrophage polarization. This study provides further insights into the mechanistic basis of ARS in UC treatment offering a potential avenue for therapeutic intervention.